2019
DOI: 10.1148/radiol.2019182135
|View full text |Cite
|
Sign up to set email alerts
|

LI-RADS Treatment Response Algorithm: Performance and Diagnostic Accuracy

Abstract: epatocellular carcinoma (HCC) is the most common primary liver malignancy and the second-most common cause of cancer-related death worldwide (1,2). For patients with stage T2 HCC who are not candidates for surgical resection, liver transplantation offers the best chance for disease-free survival (3). The limited availability of donor organs and increasing demand for these organs result in long waiting-list times, during which many patients become ineligible for transplantation because of tumor progression beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 16 publications
(12 reference statements)
5
52
0
Order By: Relevance
“…Chaudhry et al[ 60 ] reported that 81% of HCC post-TACE which were categorized as LR-TR Nonviable demonstrate 100% necrosis on pathology. Similarly, Shropshire et al[ 62 ], reported that 67%-71% of tumors categorized as LR-TR Nonviable after TAE were 100% necrotic at pathology. The reported incidence is not surprising, since the gold standard histopathology would call anything less than 100% necrotic as viable disease.…”
Section: Emerging Evidencementioning
confidence: 94%
See 3 more Smart Citations
“…Chaudhry et al[ 60 ] reported that 81% of HCC post-TACE which were categorized as LR-TR Nonviable demonstrate 100% necrosis on pathology. Similarly, Shropshire et al[ 62 ], reported that 67%-71% of tumors categorized as LR-TR Nonviable after TAE were 100% necrotic at pathology. The reported incidence is not surprising, since the gold standard histopathology would call anything less than 100% necrotic as viable disease.…”
Section: Emerging Evidencementioning
confidence: 94%
“…Inter-reader agreements are slightly lower when comparing LR TR categorization after non-radiation arterial-based therapy for HCC. Seo et al[ 61 ], in which 78.6% of tumors were treated with TACE and imaged with either CT or MRI and Shropshire et al[ 62 ] in which all tumors were treated with TAE and imaging with MRI, reported kappas of 0.69 (CT) and 0.56 (MRI), and 0.55, respectively. These differences in inter-reader agreement between thermal ablation and arterial therapy is not surprising, since the expected imaging appearance post-ablation is simpler compared to the often complex imaging features seen after transcatheter arterial based therapies.…”
Section: Emerging Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding the importance of the diagnostic performance, it is essential that the LR-TR has high interreader reliability if it is to be used for determining treatment response and deciding on a proper management strategy in patients with HCC. Prior studies have reported on the interreader reliability of the LR-TR [10][11][12][13][14][15][16][17], but their results are subject to limitations because of their relatively small sample sizes and between-study variability in the reported data. Given the increased attention to LR-TR in clinical practice, we consider it timely and important to determine the interreader reliability of LR-TR and to understand any differences among the published studies.…”
Section: Introductionmentioning
confidence: 99%